The Effectiveness of Black Mulberry Bark (Morus Nigra L.) Ethanol Extract in Reducing Blood Glucose Levels in Male Mice (Mus Musculus) Induced by Aloxan - Saritani, Ayunda Tamara Barito; Indrisari, Maulita; Sembiring, Thyrister Nina Asarya; Nurkalbi, Nuni Rismayanti; Saputra, Agil (Devotion : Journal of Research and Community Service, 2025)
Diabetes Mellitus (DM) is a disorder of carbohydrate metabolism characterized by a disruption of the body's ability to produce insulin. The bark of the black mulberry stem has a high chemical content of anthocyanins, phenolics, flavanoids and has been known to have many properties. The purpose of this study was to determine the effectiveness of ethanol extract of black mulberry stem bark (Morus nigra L.) on reducing blood glucose levels in male mice (Mus musculus). This research is included in the laboratory-scale experimental type of research. The simplicia of the black mulberry stem is macerated then produces a dry extract. Antidiabetic testing was carried out by dividing 24 mice into 6 groups, namely a healthy control group, a positive control group (glibenchlamid), a negative control group (Na CMC 0.5%), and a 10% b/v dose extract group, a 15% b/v dose extract group, a 20% b/v dose extract group, which was induced with an allocation of 130 mg/kg BB. Based on the results of research that has been carried out, ethanol extract of black mulberry stem bark at a dose of 20% b/v has the highest effect of reducing blood glucose levels with a percentage decrease of 33.51%, compared to doses of 10% and 15%, showing a percentage decrease of 5.51% and 2.36%.